2019
DOI: 10.1098/rsos.182165
|View full text |Cite
|
Sign up to set email alerts
|

Unusual echolocation behaviour of the common sword-nosed batLonchorhina aurita: an adaptation to aerial insectivory in a phyllostomid bat?

Abstract: Most insectivorous bat species in the Neotropical family Phyllostomidae glean insects from ground, water or vegetation surfaces. They use similar and stereotypical echolocation calls that are generally very short (less than 1–3 ms), multi-harmonic and frequency-modulated (FM). By contrast, the common sword-nosed bat, Lonchorhina aurita , which has the longest noseleaf in the entire phyllostomid family, produces distinctly different echolocation calls. They are composed of a constant fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Due to the unique nature of this species' echolocation, records of occurrence may emerge through future canopy surveys utilizing bioacoustics, subsequently improving our understanding of its ecological requirements. Although not present in our study area, Lonchorhina aurita represents another species from the subfamily Phyllostominae whose call Gessinger et al (2019) recently demonstrated to differ fundamentally from the stereotypical echolocation call design of the family, likely reflecting an adaptation to aerial hawking.…”
Section: Species-specific Exceptions To the General Phyllostomid Callmentioning
confidence: 75%
“…Due to the unique nature of this species' echolocation, records of occurrence may emerge through future canopy surveys utilizing bioacoustics, subsequently improving our understanding of its ecological requirements. Although not present in our study area, Lonchorhina aurita represents another species from the subfamily Phyllostominae whose call Gessinger et al (2019) recently demonstrated to differ fundamentally from the stereotypical echolocation call design of the family, likely reflecting an adaptation to aerial hawking.…”
Section: Species-specific Exceptions To the General Phyllostomid Callmentioning
confidence: 75%
“…Most of the members of Phyllostomidae family emits echolocation calls (usually of low intensity) composed of multiharmonic components and constant modulated frequencies (Gessinger et al, 2019). The adaptability to understory orientation and the similarity among echolocation calls within this diverse group of bats makes almost impossible to detect particular signatures to identify species acoustically.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptability to understory orientation and the similarity among echolocation calls within this diverse group of bats makes almost impossible to detect particular signatures to identify species acoustically. Nevertheless, we recorded species of the Glyphonycterinae, Macrotinae, Micronycterinae, and Phyllostominae subfamilies because recent descriptions of some species show that they emit intense and distinct calls that could be included in monitoring programs (Brinkløv, Kalko, & Surlykke, 2010; Geipel, Jung, & Kalko, 2013; Gessinger et al, 2019; Weinbeer et al, 2013). This is particularly important as several members of these subfamilies are known to be sensitive to habitat disruption (Clarke, Rostant, & Racey, 2005; Fenton et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophyllum macrophyllum emits calls with a timefrequency structure like other phyllostomids, but of higher intensities (Brinkløv et al, 2010). It is one of few phyllostomid bats known to use a distinct search, approach and buzz pattern in its echolocation emission during prey capture, as otherwise observed in the majority of aerial hawking and trawling bats (Brinkløv et al, 2009;Gessinger et al, 2019;Weinbeer and Kalko, 2007). These specific adaptations show that M. macrophyllum has adapted its echolocation to the hunting niche, but it is still a nose-emitting bat originating from a family dominated by gleaners.…”
Section: Introductionmentioning
confidence: 99%